(untitled) (Research, Society and Development, 2022)
The production of vegetables is characterized by the high intensity of soil use and its resources. The objective was to evaluate the growth, development, productivity and physicochemical characteristics of radish submitted to doses of organic fertilization. The experiment was conducted in the field under 70% shading conditions. A randomized block design with five repetitions and five treatments (0, 15, 30, 45 and 60 t ha-1 of bovine manure) was used. Plant height, stem diameter, number of leaves and leaf area index were evaluated 35 days after planting. Afterwards the plants were harvested and determinations of dry and fresh biomass of the aerial part and bulbs, bulb length and diameter, total soluble solids content (SS), total titratable acidity (TA), SS/TA ratio, pulp color and bulb skin color were performed. The data obtained were submitted to variance analysis (F test) at 5% significance level and presenting significant effect, regression analysis and Tukey test at 5% probability were performed. The doses 30, 45 and 60 t ha-1 did not differ and resulted in higher values for the variables yield, aboveground dry mass, fresh mass and bulb diameter. It was found that the dose of 30 t ha-1 provided higher aerial dry mass, bulb dry mass and SS/AT ratio. It was verified that fertilization with bovine manure, with dosages between 30 and 45 t ha-1 provided an increase in the culture of radish cv. Saxa cultivated under the conditions of the Brazilian semiarid region.